"I Wouldn't Start From Here"—An Alternative Perspective on PTSD From the ICD‐11: Comment on Friedman (2013). Issue 5 (22nd October 2013) - Brewin, Chris R.
<x xml:space="preserve">Abstract</x> This commentary briefly summarizes some of the criticism directed at the diagnosis of posttraumatic stress disorder (PTSD) according to the Diagnostic and Statistical Manual of Mental Disorders (5th ed.) including the issues of complexity and comorbidity, and offers a rationale for attempting a simpler approach to diagnosis that can be used in minimally resourced, non‐English‐speaking countries. Rather than describe comprehensively the features of PTSD, the World Health Organization in its upcoming edition of the International Classification of Diseases has opted to define a much smaller number of symptoms that will effectively discriminate PTSD from other related conditions. Parallel research on the two approaches to diagnosis promises to add greatly to our understanding of the condition.